2021
DOI: 10.1128/jcm.02637-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accelerate Pheno System for Rapid Identification and Antimicrobial Susceptibility Testing of Positive Blood Culture Bottles Inoculated with Primary Sterile Specimens from Patients with Suspected Severe Infections

Abstract: The Accelerate PhenoTM system (APS, Accelerate Diagnostics) is approved for the rapid identification and phenotypic antimicrobial susceptibility testing (AST) of microorganisms grown from positive blood cultures inoculated with blood from septic patients. We evaluated the performance for identification and AST from positive blood culture bottles inoculated with primary sterile non-blood specimens from patients with suspected severe infections. One hundred positive blood culture bottles with primary sterile spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A study reported correct identi cation of all bacteria of mixed cultures in 12.5-40% of cases (2,3), and in 68.8% when only bacteria included in the panel were considered (3). In another study in which sterile site specimens were inoculated in blood culture bottles, 7/9 polymicrobial cultures were wrongly identi ed as monomicrobial (24). In 6 studies investigating the clinical impact of AXDX implementation, 124 of 1444 cultures (8.6%) were found to be polymicrobial (11)(12)(13)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported correct identi cation of all bacteria of mixed cultures in 12.5-40% of cases (2,3), and in 68.8% when only bacteria included in the panel were considered (3). In another study in which sterile site specimens were inoculated in blood culture bottles, 7/9 polymicrobial cultures were wrongly identi ed as monomicrobial (24). In 6 studies investigating the clinical impact of AXDX implementation, 124 of 1444 cultures (8.6%) were found to be polymicrobial (11)(12)(13)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported correct identification of all bacteria of mixed cultures in 12.5–40% of cases [ 2 , 3 ], and in 68.8% when only bacteria included in the panel were considered [ 3 ]. In another study in which sterile site specimens were inoculated in blood culture bottles, 7/9 polymicrobial cultures were wrongly identified as monomicrobial [ 24 ]. In 6 studies investigating the clinical impact of AXDX implementation, 124 of 1444 cultures (8.6%) were found to be polymicrobial [ 11 13 , 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the new culture-based technology, Accelerate PhenoSystem (APS, Accelerate Diagnostics, Inc., Tucson, AZ, USA), allows pathogen ID and MIC values to be obtained within 2 and 7 h, respectively. The system uses the fluorescence in situ hybridization (FISH) technique for identifying common pathogens in bloodstream infections and morphokinetic cellular analysis for AST [ 43 , 45 , 48 ]. Another recent technology that allows same-day pathogen ID and AST is based on acoustic-enhanced flow cytometry [ 49 ].…”
Section: Current Methods For the Clinical Diagnosis Of Bacterial Infe...mentioning
confidence: 99%